Neuroscience in Forensic Contexts: Ethical Concerns - Morse, Stephen J. (2017)
This is a chapter in a volume, Ethics Challenges in Forensic Psychiatry and Psychology Practice, edited by Ezra E. H. Griffith, M.D. and to be published by Columbia University Press. The chapter addresses whether the use of new neuroscience techniques, especially non-invasive functional magnetic resonance imaging (fMRI) and the data from studies employing them raise new ethical issues for forensic psychiatrists and psychologists. The implicit thesis throughout is that if the legal questions, the limits of the new techniques and the relevance of neuroscience to law are properly understood, no new ethical issues are raised. A major ethical lapse would occur if practitioners use neuroscience without the proper understanding. It concludes that little new neuroscience is directly relevant at present to forensic practice and prescribes modesty and caution before employing it as the basis for expert reports and testimony in criminal and civil law cases